Liver Masses: Radiological, Histopathological, and Immunohistochemical Correlation - A Retrospective Tertiary Care Hospital-Based Study - Bhamra, Swarneet; Tiwari, Priyanka; Gupta, Bharat; Agrawal, Preeti (Annals of Pathology and Laboratory Medicine, 2024)
Background: Hepatic lesions consist of a wide range of abnormalities, including benign tumors, abscesses, primary malignancies, and metastatic tumors, each with distinctive histopathological and radiological findings. It is often challenging to differentially diagnose most metastatic lesions and some liver primaries based on clinical, radiological, and histopathological findings alone. Immunohistochemistry plays a crucial role in accurately diagnosing such lesions, which further aids clinicians in formulating an appropriate treatment plan. Materials and Methods: The present cross-sectional retrospective study was conducted in the Department of Pathology at the American International Institute of Medical Sciences, Udaipur. Data from ultrasound-guided liver biopsies received in the department between January 2022 and October 2023 were collected. Immunohistochemical data for the respective cases were also gathered. Statistical analysis was performed using MedCalc software. A p-value of <0.05 was considered the cutoff for statistical significance.. Results: A total of 82 cases were included in the study. The mean age was 58.37 years. Of the 82 cases, 80 (97.5%) were malignant, and 2 (2.5%) were benign. Among the 80 malignant lesions, 10 (12.5%) were primary hepatic tumors, while 70 (87.5%) were metastatic tumors. Sensitivity, specificity, negative predictive value, positive predictive value, and diagnostic accuracy were 50.00%, 100.00%, 98.77%, 100.00%, and 98.78%, respectively. The p-value was statistically significant (p < 0.024). Conclusion: Despite various advancements in imaging techniques, histopathological assessment followed by immunohistochemistry remains the gold standard for accurately diagnosing liver lesions. The integration and correlation of both radiological and pathological findings will provide better diagnostic accuracy, leading to improved patient care, prognosis, and overall survival.